The importance of logistics variables on port performance analysis: A DEA approach to analyzing 57 ports in the world port ranking / Rudy Eruwan Jamain, Roza Hazli Zakaria and NurulHuda Mohd Satar - Jamain, Rudy Eruwan; Zakaria, Roza Hazli; Mohd Satar, NurulHuda (Faculty of Business and Management, 2022)
Port performance is an important gateway to countries and business entities. This study aims to explore the importance of logistics variables towards port performance measurement. A standard method used to measure port performance is the analysis of its inputs and outputs based on port characteristics, such as length of berth, number of cranes, and depth. Indubitably, these approaches are among the most practical used by scholars to measure port performance. However, other external factors, such as logistical variables, need special attention, as they have been discussed in previous studies as having the capability to influence the measurement of a port's performance. As such, this study measures the technical efficiency of 57 ports, ranked among the most efficient ports globally, via a Data Envelopment Analysis (DEA) and uses sensitivity analysis to measure the impact logistics variables have on the measurement of performance. For robustness checking, the Robust Fixed Effects tool was applied to measure the impact of the logistics variables on port technical efficiency. The results show that logistics variables significantly impact the technical efficiency measurements of ports.